Epidemiological tracing of bovine tuberculosis in Switzerland, multilocus variable number of tandem repeat analysis of Mycobacterium bovis and Mycobacterium caprae. - Giovanni Ghielmetti; Simone Scherrer; Ute Friedel; Daniel Frei; Dominique Suter; Lukas Perler; Max M Wittenbrink (PLoS ONE, 2017)
BACKGROUND:After 15 years of absence, in 2013 bovine tuberculosis (bTB), caused by Mycobacterium (M.) bovis and M. caprae, reemerged in the Swiss dairy cattle population. In order to identify the sources of infection as well as the spread of the agents, molecular-epidemiologic tracing by MIRU-VNTR analysis in combination with spoligotyping was performed. A total of 17 M. bovis and 7 M. caprae isolates were cultured from tuberculous bovine lymph nodes and analyzed with a set of 49 genetic markers by using automated capillary electrophoresis. RESULTS:The outbreak in the western part of Switzerland was caused by M. bovis spoligotype SB0120. With the exception of four single-locus variations observed in MIRU 20, the MIRU-VNTR profiles of the 17 M. bovis isolates were identical, indicating a single source of infection. M. bovis detected in one archival bovine specimen from the outbreak region showed an identical MIRU-VNTR profile, suggesting persistence of the agent in a dairy herd for nearly fifteen years. The outbreak in the eastern part of Switzerland was caused by M. caprae spoligotype SB0418. All Swiss M. caprae isolates showed the Lechtal-type MIRU-VNTR profile, described as endemic in wild ruminants and in dairy cattle in Austrian bordering regions. This suggests the agent was most likely introduced by Swiss dairy cattle summering on Austrian pastures. CONCLUSIONS:The present study is the first MIRU-VNTR analysis of Swiss bTB mycobacterial isolates. The genotyping assay was found to be highly discriminating and suitable for the epidemiological tracing of further outbreaks. These findings will contribute to the development of an international MIRU-VNTR database aiming to improve bTB surveillance.